2009
DOI: 10.1021/jo900483m
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I)-Catalyzed Cascade: Direct Access to Furans from Alkynyloxiranes

Abstract: Functionalized furans are conveniently formed by a new silver(I)-catalyzed reaction of alk-1-ynyl oxiranes in the presence of p-toluenesulfonic acid and methanol. Evidence supported a cascade mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…However, it turns out that several bench available Au salts such as AuCl, Ph 3 PAuCl and a NHCAuCl(NHC = 1,3-bis(2,4,6-trimethylphenyl) imidazol-2-ylidene) are all less reactive (entries [14][15][16][17][18][19][20]. Using Ag 2 CO 3 as the catalyst, an examination on the solvent effect was then undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…However, it turns out that several bench available Au salts such as AuCl, Ph 3 PAuCl and a NHCAuCl(NHC = 1,3-bis(2,4,6-trimethylphenyl) imidazol-2-ylidene) are all less reactive (entries [14][15][16][17][18][19][20]. Using Ag 2 CO 3 as the catalyst, an examination on the solvent effect was then undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…Professor Pale and his colleagues have reported that α-alkynyl-substituted oxiranes can be converted in one step to furan in the presence of a silver catalyst, AgOTf, and an organic acid (Scheme 22) [30]. The reaction proceeds at room temperature in a DCM-methanol solvent mixture (9:1).…”
Section: Metal-catalyzed Ring Expansions Of Oxiranes To Five-memberedmentioning
confidence: 99%
“…Pale et al 25 and 1,3-diketones 28-3 depending on whether alcohol is present; a mechanism is proposed in Scheme 28. 26c In this complicated pathway, formation of difurylmethane species 28-2 is derived from the coupling of cations 28c and their alcohol derivatives.…”
Section: Scheme 25 Gold(iii)-catalysed Transformation Of Alkynyl Epoxmentioning
confidence: 99%